2005
DOI: 10.1007/s10531-004-8414-2
|View full text |Cite
|
Sign up to set email alerts
|

Littoral species diversity and biomass: concordance among organismal groups and the effects of environmental variables

Abstract: Biomass and species diversity (richness and evenness) of littoral organisms were explored in 27 sites in three basins of the large Lake Saimaa system in eastern Finland. The basins differed in degree of nutrient loading and trophic status. Six organismal groups, i.e., phytoplankton, periphyton, macrophytes, crustacean zooplankton, benthic macroinvertebrates and fish were studied. Factors affecting the biomass and diversity of these groups were explored by multiple stepwise regression analysis. The biomass of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 67 publications
5
34
1
Order By: Relevance
“…Both macrophyte PVI and extent of macrophytes lakewards were found to be associated with littoral macroinvertebrate abundance. Dense macrophyte stands support many species of macroinvertebrate, probably through increased habitat complexity, availability of food and refuge from predation (Weatherhead and James, 2001;Tolonen et al, 2003Tolonen et al, , 2005. While not surprising that metrics of littoral macroinvertebrate community richness increase with presence and diversity of macrophytes, it is important that the use of LHS is not weighted in such a way that it is effectively a surrogate for a survey of macrophytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both macrophyte PVI and extent of macrophytes lakewards were found to be associated with littoral macroinvertebrate abundance. Dense macrophyte stands support many species of macroinvertebrate, probably through increased habitat complexity, availability of food and refuge from predation (Weatherhead and James, 2001;Tolonen et al, 2003Tolonen et al, , 2005. While not surprising that metrics of littoral macroinvertebrate community richness increase with presence and diversity of macrophytes, it is important that the use of LHS is not weighted in such a way that it is effectively a surrogate for a survey of macrophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling was done in August 2006. Benthic sampling was carried out using a bilge pump suction sampler (Whale s Gusher 30) with a stiff 38 mm bore tube (after Tolonen et al, 2001Tolonen et al, , 2005. At each distance from shore, suctioning was carried out for 30 s in a transect across the habplot.…”
Section: Sampling Of Macroinvertebratesmentioning
confidence: 99%
“…Macrophytes can have dramatic effects on the physical structure of aquatic habitats (O'Hare et al, 2006;Smokorowski and Pratt, 2007) and create a heterogeneous mosaic at different scales. Some studies have suggested that structural heterogeneity of macrophytes mediates trophic interactions among various biota (Jeppesen et al, 1997;Pelicice and Agostinho, 2006) and significantly influences the biodiversity of the zooplankton community (Tolonen et al, 2005). Among animals that use aquatic macrophytes in freshwater ecosystems, zooplankton are located at an intermediate level of the food web and play a key role in transferring energy and materials within the food web (Wetzel and Likens, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Invertebrate density and therefore biomass has been shown to be positively associated with macrophyte biomass aquatic environments (Hargeby et al 1994;Palomäki and Hellsten 1996;Tolonen et al 2005). Thus, in the current study, differences in macroinvertebrate abundances may have been partly due to differences macrophyte biomass among the ponds.…”
Section: Water Quality and Insect Assemblage Structurementioning
confidence: 55%